Tympanostomy Tube Placement in Children Using a Single‐Pass Tool with Moderate Sedation. (6th June 2017) - Cofer, Shelagh; Meyer, Abby; Yoon, Daniel; Beebe, David; Castro, Chandra; Rimell, Frank; Belani, Kumar
Abstract : Insertion of tympanostomy tubes is a common elective pediatric surgical procedure and is typically performed under general anesthesia. The potential to reduce general anesthetic requirements for young children has led to increased interest in alternatives for tympanostomy tube placement. A tympanostomy tube system, developed to enable tympanostomy tube placement in a single pass on conscious patients under moderate sedation, was evaluated. A prospective study on 128 children and 253 tympanostomy tube placements conducted at 4 centers in the United States demonstrated an 88.3% success rate in performing the procedure under moderate sedation with adverse events within normal rates reported in the literature. The feasibility of completing tympanostomy tube placement under moderate sedation enables avoidance of general anesthesia and provides additional choices to physicians and parents.